Development of a Cost-Effective Process for the Heterologous Production of SARS-CoV-2 Spike Receptor Binding Domain Using Pichia pastoris in Stirred-Tank Bioreactor - Noseda, Diego Gabriel (2023)
SARS-CoV-2 was identified as the pathogenic agent causing the COVID-19 pandemic.Among the proteins codified by this virus, the Spike protein is one of the most external and -exposed.A fragment of the Spike protein, named the receptor binding domain (RBD), interacts with theACE2 receptors of human cells, allowing the entrance of the viruses. RBD has been proposed as aninteresting protein for the development of diagnostic tools, treatment, and prevention of the disease.In this work, a method for recombinant RBD production using Pichia pastoris as a cell factory in astirred-tank bioreactor (SRTB) up to 7 L was developed. Using a basal saline medium with glycerol,methanol, and compressed air in a four-stage procedure, around 500 mg/L of the raw RBD producedby yeasts (yRBD) and 206 mg/L of purified (>95%) RBD were obtained. Thereby, the proposedmethod represents a feasible, simple, scalable, and inexpensive procedure for the obtention of RBDfor diagnosis kits and vaccines’ formulation.